-9u-6=-4(u+4)

Simple and best practice solution for -9u-6=-4(u+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9u-6=-4(u+4) equation:


Simplifying
-9u + -6 = -4(u + 4)

Reorder the terms:
-6 + -9u = -4(u + 4)

Reorder the terms:
-6 + -9u = -4(4 + u)
-6 + -9u = (4 * -4 + u * -4)
-6 + -9u = (-16 + -4u)

Solving
-6 + -9u = -16 + -4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '4u' to each side of the equation.
-6 + -9u + 4u = -16 + -4u + 4u

Combine like terms: -9u + 4u = -5u
-6 + -5u = -16 + -4u + 4u

Combine like terms: -4u + 4u = 0
-6 + -5u = -16 + 0
-6 + -5u = -16

Add '6' to each side of the equation.
-6 + 6 + -5u = -16 + 6

Combine like terms: -6 + 6 = 0
0 + -5u = -16 + 6
-5u = -16 + 6

Combine like terms: -16 + 6 = -10
-5u = -10

Divide each side by '-5'.
u = 2

Simplifying
u = 2

See similar equations:

| x/2-2x/16=3/6 | | 7+5x=159 | | 8x^2-56x+48=0 | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)x(1/7) | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)X1/7 | | -7(w-3)=-5w+27 | | 3/10=-4/1-1/5 | | 0.14=4/80 | | 1-3x-x^3=2x+1 | | -y=-6x+7 | | 10y+36-38y-47= | | 6.673-(-8.29)=-1.617 | | -6a^7+3a^4-a= | | -20/21*21 | | 17x=0.0005 | | 1/2m=7/8 | | 3.1x^2+x^2=4.9x^2 | | 3t/4-t/3=7-1/6 | | -(5u-v-6)= | | lg(x)=0.04084 | | 3a(a-2)+a=2(a+1) | | 3q/4-5=5q/8 | | f/8-1=2 | | P/6=5-2p/3 | | 8+3x+4x=10x-1 | | 9x+7=8x-12 | | 5z/6-7z/12=6 | | 5(3x-5)+2(3x+2)= | | 51+38=x | | 5z/6-7z/12 | | r(x)=3 | | 3x^2-5x-1=o |

Equations solver categories